Pathology and prognostic factors of conjunctival melanoma - Berta-Antalics, A. I.; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2015)
Conjunctival melanoma is a rare but potentially fatal disease. The 10-year melanoma mortality can be up to 30 %, recurrence rates after treatment up to 50 % and the overall incidence of metastasis is 26 %. Improved treatment options are needed to increase the tumor-free survival of affected patients.The aim of the study was to perform clinical and pathological staging using the TNM classification and to correlate the results with treatment modalities and recurrence rates.The study included a case series of 80 eyes from 80 patients (42 females and 38 males, age 28-90 years) with histopathologically proven conjunctival melanoma studied by reviewing medical records, pathology reports and color photographs. The main evaluated characteristics were demographic information, tumor size, thickness, pathological diagnosis, BRAF mutation testing, clinical and pathological staging, recurrence, metastasis and duration of follow-up (mean 48 months).The lesions predominantly involved the bulbar conjunctiva (60 %) and other sites that were less often involved were the palpebral conjunctiva (23 %), conjunctival fornix (22 %) and lacrimal caruncle (15 %). Of the tumors 36 % were TNM classified as pTis, 34 % as pT1, 20 % as pT2 (palpebral, fornix and caruncle) and 10 % as pT3. Local recurrences were noted in 36 % of the patients (18 % Tis, 26 % T1, 32 % T2 and 70 % T3) and regional and distant metastasis in 20 % of the patients (0 % Tis, 10 % T1, 15 % T2 and 60 % T3).In this study increasing T stages were more often associated with recurrences and metastasis. Future studies correlating the TNM staging with histopathological and genetic predictors may help to improve the management of patients with conjunctival melanoma.
EVALuna2:21241